2013
DOI: 10.1103/physrevlett.110.087004
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Mass Enhancement and Temperature Dependence of the Electronic Structure of FerromagneticSrRuO3Thin Films

Abstract: We report high-resolution angle-resolved photoemission studies of epitaxial thin films of the correlated 4d transition metal oxide ferromagnet SrRuO3. The Fermi surface in the ferromagnetic state consists of well-defined Landau quasiparticles, exhibiting strong coupling to low-energy bosonic modes which contributes to the large effective masses observed by transport and thermodynamic measurements. Upon warming the material through its Curie temperature, we observe a substantial decrease in quasiparticle cohere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
80
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 38 publications
(42 reference statements)
12
80
3
Order By: Relevance
“…The large hole pocket at k=Z is indeed observed in the ARPES experiment. [12] As shown in the SM, the orbital character of this hole pocket at k=Z is xy and yz, which is consistent with the suggestion from the ARPES experiment. [12,29,34] On the other hand, ARPES shows a kink feature in the spectral function at 65 meV below E F along Γ and Z.…”
supporting
confidence: 88%
“…The large hole pocket at k=Z is indeed observed in the ARPES experiment. [12] As shown in the SM, the orbital character of this hole pocket at k=Z is xy and yz, which is consistent with the suggestion from the ARPES experiment. [12,29,34] On the other hand, ARPES shows a kink feature in the spectral function at 65 meV below E F along Γ and Z.…”
supporting
confidence: 88%
“…In addition, the photoemission and optical conductivity measurements have recently revealed that the duality of itinerant and localized natures appears even in pure SrRuO 3 . 49,50) The δ values estimated from the frequency dependence of T * indicate that the low temperature ordered phase for x ≥ 0.3 can not be realized to a spin-glass but a cluster-glass state. Furthermore, the present dc-magnetization curves measured in the field cooled conditions are clearly incompatible with those expected from the spin-glass system ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have strong reasons to believe that a significant part of the experimental mass enhancement comes from electron-boson coupling. In fact, recent ARPES measurements by Shai et al 42 reveal a kink in the spectra, in the vicinity of the Fermi level, which is a text-book example of electron-boson coupling, most likely magnons. This contribution is not considered in the single-site LDA+DMFT approach, which includes uniquely electronic contributions.…”
Section: Effects Of On-site Coulomb Interactionmentioning
confidence: 99%